STUDYING OF LAWS PHYSIC BY MEANS OF VIRTUAL COMPUTER MODELS - Saparbayeva, T.; Kahhorov, S. K. (Recent Contributions to Physics, 2017)
The paper is devoted to study the laws of physics with the help of computer models.